Classical Music Improves Children's Learning Concentration in Kindergarten - Rika Rahwati; Diana (LPPM Undiksha, 2025)
Children who have difficulty concentrating during play-learning activities. Factors such as noise, visual disturbances, or irrelevant social interactions can distract them. This study aimed to analyze the application of classical music to improve children's concentration in kindergarten. This study used a quantitative method with an experimental design. This study focused on all kindergarten students. The sample used was 40 students aged 4 to 6 years. These students were selected using purposive sampling. The methods used in collecting data were questionnaires, literature studies, and documentation. The instruments used in collecting data were questionnaire sheets. This study analyzed data using inferential statistical techniques. The results of the study were that the 4-5 year age group showed an increase in the average score from 11.05 to 15.65, resulting in an N-Gain of 0.45 (moderate category), while the 5-6 year age group increased from 10.15 to 17.85, reaching an N-Gain of 0.79 (high category). Regression analysis revealed that classical music significantly impacted children's concentration, with a regression coefficient of 0.674 and a significance value of 0.010. It was concluded that classical music was proven to increase selective attention, resilience in maintaining focus, and the ability to ignore external distractions. Thus, integrating classical music into early childhood education can effectively improve the quality of the learning experience process. The implication of this research is that the use of classical music can help children's learning activities.